Righteousness of hearts is the way to salvation to God - Abdullah, Hassan Allawi (Arab Journal for Sciences and Research Publishing, 2016)
Praise be to God, prayer and peace be upon the Messenger of Allah (God bless him). The research includes on two topics cover in the first section: Deliverance definition language and idiomatically and study the statistical verses of deliverance. The second topic: I spoke about the impact of Deliverance in goodness of heart, and the aim of the search, because things are mixed up in a time when they became the people is to deliverance from miserable existence, highlights the importance of this research extensively studied in one of the important Koran that determine ways to deliverance the worries from minimum life. we concluded that deliverance It is not able without the goodness of hearts ,that the fear from God was the most important actions of the heart, that piety is the permanent intake in the minimum life , that it was the reason of happiness and the way of win to paradise, that sincerity intention is the cause of acceptance and the basis of all the work, so that most to be self-accounting and dependence to God , that the deliverance depends on the hearts action in first degree .The human actions could be without any value if not be stems from the heart ’so it was this research shows you how to deliverance by the goodness of heart.